PETROLOGI BATUAN OFIOLIT DAERAH SODONGPARAT, KAWASAN CILETUH, SUKABUMI - Rosana, Mega F.; Yuningsih, Euis T.; Saragih, Kessar D.; Ikhram, Rinaldi; Ardiansyah, Nugraha (Fakultas Teknik Geologi Universitas Padjadjaran, 2015)
Ophiolite outcrops offers a unique opportunity to learn directly oceanic lithosphere, as ophiolite represents one of the few outcrops of rock that body can not be reached. Ophiolite is interpreted in the context of plate tectonics, as part of the oceanic lithosphere thrust into the continent during the first phase of orogenesa. Many geologists believe that the definition of ophiolite according to Penrose Field Conference in 1972, which is a typical sequence of rocks composed of, starting from the bottom: the complex ultramafic, gabbro complex, complex sheeted mafic dikes, complex mafic-volcanic and sedimentary pelagos. Ophiolite sequence may be incomplete, torn or termetamorfisme. Group ophiolite in area Ciletuh is an assemblage of mafic rocks (basalt, gabbro and ultramafic (peridotite, serpentinite), which is closely associated with the sedimentary-volcanic and metamorphic rocks. Generally ofiolitnya a sequence ophiolite very incomplete, and the mechanism of the transferor-tempatannya (emplacement ) can be equated with ophiolite